Behavioral evidence that segregation and representation are dissociable hippocampal functions - Kubík, Štěpán; Fenton, A. A (The Journal of neuroscience, 2005)
Hippocampal activity is thought to encode spatial representations in a distributed associative network. This idea predicts that partial hippocampal lesions would spare acquisition and impair retrieval of a place response as long as enough connections remained intact to encode associations. Water maze experiments supported the predictions, but the prediction of impaired retrieval was not supported when tetrodotoxin (TTX) was injected into one hippocampus and rats were tested in a place avoidance task on a rotating arena with shallow water. The rotation dissociated relevant distal stimuli from irrelevant self-motion stimuli. To explain the discrepancy, we hypothesized that the segregation of relevant and irrelevant stimuli and stimuli association into representations are distinct hippocampus-dependent operations, and whereas associative representation is more sensitive to disruption during retrieval than learning, stimulus segregation is more sensitive to disruption during learning than during retrieval. The following predictions were tested: (1) the TTX injection would spare learning but (2) impair retrieval of a place response in the water maze, which has a high associative representational demand but a low demand for segregation; (3) the injection would impair learning but (4) spare retrieval of place avoidance in the rotating arena filled with water, which has a high demand for stimulus segregation but a low associative representational demand. All four predictions were confirmed. The hypothesis also explains the pattern of sparing and impairment after the TTX injection in other place avoidance task variants, leading us to conclude that stimulus separation and association representation are dissociable functions of the hippocampus.
Keywords: časové faktory; Male; Rats; Analysis of Variance; anestetika lokální; chování zvířat; potkani Long-Evans; úniková reakce; vnímání prostoru; Escape Reaction; Memory Disorders; Financing, Organized; Animals; Hippocampus; zvířata; Maze Learning; Time Factors; Avoidance Learning; hipokampus; mužské pohlaví; analýza rozptylu; bludiště - učení; financování organizované; Tetrodotoxin; Mental Recall; Behavior, Animal; krysa rodu Rattus; Space Perception; rozpomínání; učení vyhýbat se; Anesthetics, Local; poruchy paměti; Rats, Long-Evans; tetrodotoxin